Contributions to the knowledge of Olixon Cameron, 1887 (Hymenoptera, Rhopalosomatidae): a new species and new records of the genus for northeastern Brazil - Celante, Gabriel Luiz; Carvalho, Adhan Gabriel; Martins, André Luis; Bulbol, Mayara Medeiros; Brito, Amaury Soares De; Teodoro, Adenir Vieira; Jahyny, Benoit Jean Bernard (Zootaxa, 2025)
The genus of solitary wasps Olixon Cameron, 1887 is currently represented by 29 species, distributed across the African, Australian and American continents where it is present from southeastern Canada to central-eastern Argentina for the latter. Its presence in India is also attested. Despite the many genus records published for the Neotropical region, northeastern Brazil is still one of the least represented regions for the genus. Here we describe and illustrate Olixon caju Celante, Martins & Bulbol, sp. nov., based on specimens of both sexes collected in a Restinga vegetation located in the coastline of the state of Sergipe, Brazil. In this work the description was carried out based on a male, with, additionally, the description and illustration of the genitalia. We provide an updated identification key for the seven New World species and present a distribution map for the three known species that occur in Brazil including new distribution records for Olixon testaceum Cameron, 1887 in northeastern Brazil.